Use of Industrial Control Unit in Intelligent Homes - Brožek Josef; Fiala Vladimír; Fikejz Jan; Pich Pavel (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The work focuses on using of industrial unit in intelligent homes.
Využití průmyslové řídící jednotky v inteligentní domácnosti
Keywords: Use; Industrial; Control; Unit; Intelligent; Homes; Využití; průmyslové; řídící; jednotky; inteligentní; domácnosti